Pemberdayaan Pemahaman Masyarakat Dalam Mengoptimalkan Peluang Keuangan - Vaneza Sabatimy; Dhani Ichsanuddin Nur (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Investment is the act of buying or placing capital into an asset or project with the aim of obtaining future profits. Another goal of investment is to achieve a greater return on investment compared to the invested capital amount. The higher the investment risk, the higher the potential returns, while conversely, lower investment risks result in lower returns. Investment can serve as one of the ways to aid in financial preparation for the future and achieve long-term financial goals.